Implemention Of Rahn Tasjily For The Benefit Of The Community Peureulak Pawnshop, East Aceh - Hoessien, Jalaluddin (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2026)
The requirements of society will dictate how economic practices develop. Efforts to create the Islamic economy revolve on the idea of maslahah. The central focus of this study is to analyze the current Islamic pawn system and its application of the notion of Rahn within the framework of Islamic law. Rahn, whose root meaning is